Partially bio-based thermoplastic elastomers by physical blending of poly(hydroxyalkanoate)s and poly(ethylene-co-vinyl acetate) - P. Ma; X. Cai; M. Chen; W. Dong; P. J. Lemstra (eXPRESS Polymer Letters, 2014)
Partially bio-based thermoplastic elastomers (bio-TPE) were designed and prepared by physical blending a commercial grade poly(hydroxyalkanoate)s (PHBM, Metabolix) and poly(ethylene-co-vinyl acetate) (EVA). The PHBM is miscible with EVA90 which has a vinyl acetate (VA) content of 90 wt% while it is not miscible with EVA at low VA content (!70 wt%). The PHBM/EVA90 blends exhibit high tensile strength and typical thermoplastic elastomeric characteristics e.g. high elongation at break (>800%), good strain-recovery (>60%) and melt processability. The spherulite growth rate of PHBM decreases with increasing EVA90 content. Consequently, a large number of fine PHBM spherulites were formed in the blends. The spherulites act as physical crosslink-points leading to a thermoreversable network in the blends. Such network and elastic EVA90 molecules result in the thermoplastic and elastomeric characteristics of the PHBM/EVA90 blends.